A Comparative Analysis of Buddhist Ethics with Modern Democracy - Shrestha, Sanu Kumar (KMC Research Journal, 2025)
The fundamental purpose of this study is to compare Buddhist ethics with contemporary democracy and election procedures. Politicians, academics, and the general public rarely accept Buddhist democratic voting and dispute-solving methods. Buddhist communities have historically demonstrated democratic practices, but there is a significant gap in understanding their application in contemporary contexts. The investigation employed a hermeneutic framework and used theme analysis, a qualitative data analysis technique, to analyze the content of the literature review. The teachings of the Buddha are regarded as the cornerstone of contemporary democratic thought, which was first formed in South Asia before spreading to other parts of the globe. In both republican governments and Buddhist sanghas, the Buddha emphasized the value of representative voting as a democratic process that promotes democracy, humanist principles, and peace. The Buddhist theory has significant democratic implications because it is not a Western creation. Buddhist doctrine, which placed a high value on public institutions, accountability, transparency, and integrity, served as the foundation for the democratic government and assembly. It also had a big influence on vital social innovations and promoted freedom. The study concentrated on how important it is for the government, researchers, Bhikkhu Sangha, and the community to adopt Buddhist democratic norms and ethics because they encourage inclusive participation, accountability, transparency, and responsibility for governance. Future research should explore the integration of Buddhist-influenced government models into modern democracies to address existing systems of inefficiency.